Visual Needs - Miller, Olga; Ockelford, Adam (London Continuum, 2005)
A handy guide to the issues of teaching children with varying visual needs. Compact, practical and full of top tips, this is a guide for all teachers - whether newly qualified or more experienced - who have struggled to find sensible advice before.
Include References and Bibliography.
Keywords: Great Britain -- Children with visual disabilities--Education -- Vision disorders